Indonesia’s Extraterritorial Obligation to Protect The Human Rights of Individuals from Transboundary Haze Pollution - Bratajaya, Yogi; Christianti, Diajeng Wulan; Siswandi, Ahmad Gusman Catur (UI Scholars Hub, 2022)
Ever since the late 1980s, forest fires located in Indonesia have resulted in haze pollution which engulfs the Southeast Asian region almost annually. This paper argues that Indonesia is extraterritorially obligated to ensure the human rights of individuals outside its territory as a result of its failure to prevent the haze pollution. It analyzes the extraterritorial application of Article 2(1) of the International Covenant on Civil and Political Rights (ICCPR), arguing that an individual whose human rights have been adversely affected by transboundary environmental harm is deemed ‘subject to the jurisdiction’ of the originating state. Applying this interpretation, individuals located outside Indonesia’s sovereign territory who have been adversely impacted by haze pollution may be deemed “subject to the jurisdiction” of Indonesia for the purpose of Article 2(1) of the ICCPR. Indonesia would thus be obligated by the ICCPR to ensure protect human rights by preventing and mitigating the transboundary haze pollution.